Traslocare, riaggregare, rifondare - Gianni, Galeota (Firenze University Press, 2006)
This book recounts the phases in the set-up of the new Library of Social Sciences of the University of Florence. The move provided the opportunity for bringing together the collections that were scattered over seven service points and in about a dozen other sites closed to the public. At the same time, it provided the opportunity for reconsidering the services on offer, reorganising them on the basis of the characteristics of the new site. The first section tells how the library was conceived and planned, with the librarians' working groups preparing the move and projecting the changes to be made in the new site. The second part tackles the problems of organisation and management of the services in the new library.